10 MHz boost converter with subthreshold voltage startup and predictive dead‐time techniques for energy‐harvesting systems. Issue 10 (1st August 2020) - Huang, Wenbin; Liao, Xufeng; Liu, Lianxi
Abstract : A 10 MHz synchronous boost converter with the subthreshold startup scheme and predictive dead‐time control for energy‐harvesting systems is presented in this study. The input feed‐forward technique is adopted to achieve a fast line response, and a three‐stage startup technique is proposed to realise subthreshold voltage startup without using any extra startup circuits or special devices. Moreover, the efficiency of the high‐frequency converter can be improved by the proposed predictive dead‐time control with a high resolution of ∼300 ps. The proposed converter is implemented in a standard 0.18 μm complimentary metal oxide semiconductor process and occupies a die area of 1.4 × 1.5 mm 2 . Experimental results show that the input voltage ranges from 0.3 to 1.5 V at 1.8 V output, and the minimum startup voltage is 0.3 V. Under V IN  = 1.5 V, V OUT  = 1.8 V and 150 mA load, the power efficiency can be improved by 2.6% because of the proposed predictive dead‐time control. The peak efficiency can reach 90.7% under V IN  = 1.5 V. The line transient response can be improved with small overshoot voltage at the output.